(untitled) (Práxis Educativa, 2009)
The failure of the prison system has been aimed as one of the largest problems of the Brazilian repressive model. The convicts are correspondents to the jail with the purpose of rehabilitating them to the social conviviality, however, when coming back to the society, that individual will be more indifferent, unprepared, unsettled, and many times more uninhibited for the practice of another crimes. That glance reveals the presentation of a chess, of a public chain, or even of a state penitentiary. The purpose of the present work, though, it is to present another glance, based on researches accomplished in the state penitentiary of maximum safety of the city of Ponta Grossa, in the State of Paraná. It is a partnership between the public and private sector, denominated Double Responsibility or Coadministration being the administration of the prison and the education under the state government’s responsibility and the installment of services that it includes internal safety, social attendance, doctor and psychological among other, to position of a private company. Keywords: Education of Young and Adults. Public politics. Private penitentiaries. Social recuperation.